GOD WHO SAW ME: FAITH AND DEHUMANIZATION OF EXEGESIS STUDIES GENESIS 16 - Irawati, Chandra Wahyuni (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2022)
The story of Abram and Sarah is an interesting story to discuss. Chaotic household trips due to the issue of Sarah's infertility became a crucial problem that saddened both of them. In the ancient world, Sarah's barrenness was not only considered a disgrace in the family, but also a serious problem for Abram as a man who would have no heir. Impatience awaits offspring, and Sarah's suggestion for Abram to take Hagar turns out to be a domestic conflict and oppression of Hagar, the servant. But God's grace did not only apply to Abram and Sarah but also to Hagar.